Effects of pelleting low-lysine diets with fermentation products for weanling pigs - Joe D Hancock; Daniel Y.C. Fung; R A Hart; M T Manninen (Kansas Agricultural Experiment Station Research Reports, 1991)
One hundred twenty pigs (13.2 lb avg initial wt) were used in an experiment to determine the effects of pelleting on the ability of fermentation products to improve growth performance of nursery-age pigs fed low-lysine diets. Treatments were: 1) positive control (1.15 and .95% lysine for d 0 to 14 and 14 to 35, respectively); 2) diet 1 pelleted; 3) low-lysine regimen (1.05 and .85% lysine for d 0 to 14 and 14 to 35, respectively) supplemented with fermentation product (FP)l; 4) diet 3 pelleted; 5) low-lysine regimen supplemented with modified fermentation product (MFP)2; and 6) diet 5 pelleted. For pelleting, the diets were pre-conditioned to 131Â°F and pelleted (5/32" diameter pellets) at an avg production rate of 3,550 lb/h, with an avg exit temperature of 144oF. The pigs were allowed to consume feed and water ad libitum during the 35-d experiment. For d 0 to 7 and 0 to 14, pigs fed the pelleted diets had greater ADO and efficiency of gain than pigs fed diets in meal form. At d 14, apparent digestibilities of DM and N of the control diet were increased by pelleting, but those of the diets with fermentation products added were not affected. CFUs of lactobacilli, streptococci, and coliforms in feces were not affected by treatment. From d 14 to 35, pigs fed pelleted diets were more efficient but consumed less feed and had lower ADG than pigs fed diets in meal form. For d 0 to 35, ADG was not affected by treatment, but pigs fed pelleted diets consumed 8% less feed and had 8% greater efficiencies of gain than pigs fed diets in meal form. Growth performance of pigs fed the low-lysine diets plus the fermentation products was not different than that of pigs fed diets with adequate lysine concentrations. Performance of pigs fed FP or MFP was not different. At d 35, CFUs of lactobacilli in feces were not affected by treatment. CFUs of streptococci were greater for pigs fed the control diet than for pigs fed the treatment diets, but were decreased by pelleting the control diet, whereas pelleting the treatment diets increased CFUs of streptococci in feces. CFUs of coliforms were greater for pigs fed diets with MFP than those fed diets with FP. In conclusion, growth performance of pigs fed low-lysine diets plus fermentation products was equal to that of pigs fed diets with adequate lysine concentrations.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Lysine; Probiotic; Starter; Digestibility; Performance; Fecal microbes